2023
DOI: 10.1021/acs.est.3c00947
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation of Per- and Polyfluoroalkyl Ether Acids and Other Per- and Polyfluoroalkyl Substances by Sulfate and Hydroxyl Radicals: Kinetic Insights from Experiments and Models

Abstract: Per- and polyfluoroalkyl substances (PFAS) are widely used anthropogenic chemicals. Because of the strength of the carbon–fluorine bond, PFAS are not destroyed in typical water treatment processes. Sulfate (SO4 •–) and hydroxyl (•OH) radicals can oxidize some PFAS, but the behavior of per- and polyfluoroalkyl ether acids (PFEAs) in processes involving SO4 •– and •OH is poorly understood. In this study, we determined second-order rate constants (k) describing the oxidation of 18 PFAS, including 15 novel PFEAs, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 54 publications
0
18
0
Order By: Relevance
“…18 A previous TOP assay of various fluoro ether structures by Zhang et al 19 found that only H-containing structures could be converted by HO • , but the product information remained largely unknown. 20 The findings presented above reflect several limitations (but not necessarily disadvantages) of the current TOP assay. First, HO • oxidation requires H atoms in the precursor and does not transform either PFCAs or PFSAs.…”
Section: ■ Introductionmentioning
confidence: 74%
See 4 more Smart Citations
“…18 A previous TOP assay of various fluoro ether structures by Zhang et al 19 found that only H-containing structures could be converted by HO • , but the product information remained largely unknown. 20 The findings presented above reflect several limitations (but not necessarily disadvantages) of the current TOP assay. First, HO • oxidation requires H atoms in the precursor and does not transform either PFCAs or PFSAs.…”
Section: ■ Introductionmentioning
confidence: 74%
“…We recommend (i) pretreating the samples with both HO • and SO 4 – • (and sequential treatment, if needed) before target PFAS analysis, (ii) adding more known structures (e.g., – OOC–C n F 2 n –COO – , ether carboxylates/sulfonates, and other commercially available PFAS chemicals) to the target list of TOP assay, (iii) using advanced mass spectrometry methodologies, data processing algorithms, and additional spectroscopy methods (e.g., 19 F NMR) to assist structural determination, and (iv) modifying the existing methodologies with new structural transformation mechanisms. In order to satisfy the imminent need for the detection, monitoring, and treatment of “non-legacy” PFAS pollutants, it is imperative to expand our understanding of structure-transformation relationships for emerging PFAS chemicals. , The elucidation of additional transformation pathways for SO 4 – • oxidation is equally important and intriguing to environmental chemists. The currently unknown SO 4 – • oxidation TPs might soon become the “signature” of certain PFAS pollutants.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations